THE STUDY OF LEADERSHIP EFFECTIVENESS ON KINDERGARTEN HEADMASTER AT RAJEG DISTRICT, TANGERANG REGENCY - Muzayanah MUZAYANAH; Ihsana El KHULUQO (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2018)
The purpose of this research was to analyze, test and find out: (1) The direct effect of Effectiveness of Principal Leadership on Teacher Competency Kindergarten in Rajeg District Tangerang Regency; (2) The direct effect of Teacher's Achievement Motivation on Teacher Competency Kindergarten in Rajeg District Tangerang Regency; and (3) The direct effect of Effectiveness of Principal Leadership on Teacher's Achievement Motivation Kindergarten teachers in Rajeg District Tangerang Regency. Based on the results of the analysis, it was known that: (1) There was a positive and significant direct influence of the principal's leadership on teacher competency Kindergarten in Rajeg District Tangerang Regency. (2) There was a positive and significant direct influence on the achievement motivation of teacher competency Kindergarten in Rajeg District Tangerang Regency. (3) There was a positive and significant direct influence of the principal’s leadership on Kindergarten achievement motivation in Rajeg District Tangerang Regency.